2017
DOI: 10.23884/mejt.2017.2.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Data Clustering Based on the Whale Optimization

Abstract: ABSTRACT:Data clustering has emerged as a major problem in areas such

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The intracluster distance function and standard deviation values showed that the whale optimization algorithm could be successfully applied in solving the clustering problem. Canayaz and Özdağ [22] obtained a feature vector called BEST in their proposed method by applying clustering with WOA. They applied clustering by calculating the Manhattan distance between this vector and the test data.…”
Section: Introductionmentioning
confidence: 99%
“…The intracluster distance function and standard deviation values showed that the whale optimization algorithm could be successfully applied in solving the clustering problem. Canayaz and Özdağ [22] obtained a feature vector called BEST in their proposed method by applying clustering with WOA. They applied clustering by calculating the Manhattan distance between this vector and the test data.…”
Section: Introductionmentioning
confidence: 99%